Changing trends in the prevalence of childhood asthma over 40 years in Greece. Issue 10 (20th July 2021) - Ntzounas, Alexandros; Giannakopoulos, Ioannis; Lampropoulos, Panagiotis; Vervenioti, Aggeliki; Koliofoti, Eleana‐Georgia; Malliori, Styliani; Priftis, Kostas N.; Dimitriou, Gabriel; Anthracopoulos, Michael B.; Fouzas, Sotirios
Abstract: Background: A series of repeated questionnaire surveys among 8‐ to 9‐year‐old school children in the city of Patras, Greece, demonstrated a continuous rise in the prevalence of wheeze/asthma from 1978 to 2003, with a plateau between 2003 and 2008. We further investigated wheeze/asthma trends within the same environment over the last decade. Methods: Two follow‐up surveys were conducted in 2013 ( N  = 2554) and 2018 ( N  = 2648). Physician‐diagnosed wheeze and asthma were analyzed in relation to their occurrence (recent‐onset: within the last 2 years; noncurrent: before 2 years; persistent: both prior and within the last 2 years). In 2018, spirometry was also performed in participants reporting symptoms and in a sample of healthy controls. Results: The prevalence of current wheeze/asthma declined from 6.9% in 2008% to 5.2% in 2013% and 4.3% in 2018. The persistent and noncurrent wheeze/asthma groups followed this overall trend (P‐for‐trend <0.001), while the prevalence of recent‐onset wheeze/asthma remained unchanged (P‐for‐trend >0.05). Persistent and noncurrent wheezers were also more frequently diagnosed with asthma, in contrast to those with recent‐onset wheeze. The FEV1 z‐score was less than –1 in 32.1% of children with recent‐onset and in 22.4% of those with persistent wheeze/asthma; both rates were higher than those of the Noncurrent wheeze/asthma group (7.1%; p  < .05) and of healthy controls (3.5%; p  < .001). Conclusions: The prevalence of childhood wheeze/asthma has declined significantly during the last decade in Greece. The reversing trend may in part be attributed to changing asthma perceptions among physicians and/or parents, especially in the case of younger children with troublesome respiratory symptoms.